Prilagoditve domačega okolja - uporaba ocenjevalnega instrumenta ocena potencialnih ovir v domačem okolju (OPODO) pri osebah z okvaro hrbtenjače - Šuc, Lea (Rehabilitacija (Ljubljana), 2019)
Background: Assessments of the home environment and the patient's abilities to live independently after discharge from the hospital are an important part of the occupational therapy assessment. Yet, there is a shortage of standardised and reliable assessment methods for this field. Internationally, the Housing Enabler (HE) proved to be a valid and reliable screening tool for the assessment of barriers in the home environment and the surrounding areas. Methods: The HE was translated into Slovenian language and administered with 30 patients with a spinal cord injury. The patients were divided into three groups, 10 patients in each group: (1) home visit was completed with the patient, (2) home visit was completed without the patient, (3) the occupational therapist gave recommendations based on photographs. Using descriptive statistics, we analysed the frequency of environmental barriers. The three groups were compared using one-way analysis of variance and the exact Kruskal-Wallis test. Results: In the section on the outdoor environment, access to the building was the most frequently mentioned barrier, with 73% of the participants having uneven surfaces leading to their building. The entrances section most often mentioned that the stairs did not meet the criteria regarding the bannister (70%) and/or there was a high curb at the front door. In the indoor environment section, the most often mentioned barrier was that the controls and home appliances were operated by hands. There were no statistically significant differences between the three groups. Conclusions: The HE enables data collection that could be useful when planning and evaluating occupational therapy treatment. Additional training is required before using the instrument. We need to explore how to advise patients and their families regarding the adaptations of the home environment in the most efficient way.
Keywords: delovna terapija; domače okolje; environmental assessment; home environment; home visits; obisk na domu; Occupational therapy; poškodba hrbtenjače; prilagoditev okolja; rehabilitation; Spinal Cord Injuries; spinal cord injury